Predicting the efficacy of glucocorticoids in pediatric primary immune thrombocytopenia using plasma proteomics - Cao, Qingqing; Zhu, Haiyan; Xu, Wei; Zhang, Rongrong; Wang, Yun; Tian, Zhaofang; Yuan, Yufang (Frontiers in Immunology, 2023)
Primary immune thrombocytopenia (ITP) is the most common acquired autoimmune bleeding disorder among children. While glucocorticoids are the primary first-line treatment for ITP treatment, they prove ineffective in certain patients. The challenge of identifying biomarkers capable of early prediction regarding the response to glucocorticoid therapy in ITP persists. This study aimed to identify ideal biomarkers for predicting glucocorticoid efficacy in patients with ITP using plasma proteomics. A four-dimensional data-independent acquisition approach was used to analyse plasma samples in glucocorticoid-sensitive (GCS) (n=18) and glucocorticoid-resistant (GCR) (n=17)children with ITP treated with prednisone. In our investigation, 47 differentially expressed proteins (36 upregulated and 11 down-regulated) were identified in the GCR group compared with the GCS group.The significantly differentially expressed proteins myosin heavy chain 9 (MYH9) and fetuin B (FETUB) were selected for enzyme-linked immunosorbent assay validation. The validation results were consistent with the proteomics analyses and confirmed MYH9 and FETUB as promising biomarkers for predicting glucocorticoid efficacy in ITP. Furthermore, our analysis of receiver operating characteristics curves, calibration curves, and clinical decision curve analysis demonstrated good diagnostic efficacy of these validated biomarkers. This study contributes to the establishment of objective biological indicators for precision therapy in children with ITP. More importantly, these biomarkers hold potential as a foundation for making informed decisions regarding alternative treatments for drug-resistant patients, thereby preventing treatment delays.